Analyzing the Coastal Development Pattern of Tourism in Turkey - Ferhan Gezici; Ayfer Yazgan Gul; Elif Alkay (European Regional Science Association (ERSA), 2006)
The coastal concentration of tourism activities has been the main characteristics of the Mediterranean Countries. However, they are working on new approaches and solutions for the problems of coastal areas since they have faced a decrease in their high shares of the world tourism market. Although Turkey, as one of the Mediterranean Countries, is endowed with a variety of tourist attractions, it still does not receive the expected revenue from the tourism industry. Since the beginning of tourism planning in Turkey, the coastal regions have taken priority for tourism investments and not only the spatial pattern but also the socio-economic life of these regions have been transformed. According to the studies of the State Planning Organization (SPO) on socio-economic development level, coastal provinces along the Aegean and Mediterranean Seas, which have concentrated on tourism activities, indicate positive socio-economic development index values. In this paper, coastal-led development pattern of tourism is analyzed in Turkey based on the main indicators (tourism and economic development indicators). However, it seems that coastal tourism development pattern is similar for all the provinces, it will be examined if there are some clusters and typologies among them in terms of tourism development. After putting forward a historical perspective and descriptive frame for the coastal provinces and districts, the principal component analysis will be conducted in order to see the main components. The relationship between the trends of supply and demand side of tourism and the development level will be put forward in order to realize the significance of economic sustainability of tourism areas. Furthermore, the results will be evaluated considering tourism policy of Turkey and experiences of other Mediterranean Countries.
Keywords: 330